A prediction model for fatigue crack growth using effective cyclic plastic zone and low cycle fatigue properties. (June 2016) - Shi, K.K.; Cai, L.X.; Qi, S.; Bao, C.
Highlights: Effective CPZ can be regarded as FPZ in the analysis of Mode-I fatigue cracking. Relationship between LCF and FCG is developed considering crack closure. FCG model is proposed based on effective cyclic plastic field and LCF. Good agreement between predictions and experimental data is found. Abstract: Since there exists the crack closure phenomenon near the fatigue crack tip, it has an important role in the analysis of fatigue failure life. Considering the empirical crack closure expression, the effective cyclic plastic zone is developed in the present study. According to the fatigue failure criteria of plastic strain energy ahead of the fatigue crack tip, a theoretical model for fatigue crack growth rate is then established based on the effective cyclic plastic zone and the low cycle fatigue properties. The prediction results are compared with experimental data under the constant amplitude loading, and comparative results demonstrate that the fatigue crack growth rate estimated by the theoretical model closely approximates the experimental results.